Emerging trend and pattern of urbanization and its contribution from migration in Gujarat: Evidence from district level analysis - Roy, Anil Kumar; Saha, Meghnad (Frontiers in Sustainable Cities, 2023)
Gujarat has been one of the leading states in India as far as the levels of urbanization are concerned. This is due to its pull factors attracting migrations from outside the state. However, the urban population is concentrated in a few districts dominated by large urban centers such as Ahmedabad, Surat, Rajkot, Vadodara, Bhavnagar and Jamnagar. The levels of urbanization in Gujarat have been higher than the national average throughout independent India. It has also experienced rapid urban growth of population during the same period, but the recently emerging concentration and pattern of urbanization have been lopsided, meaning that a few districts contributes more than half of the total urban population of the state. Literature in the thematic areas of urbanization particularly in Gujarat are few and limited. The studies so far have discussed about the impact of globalization and urbanizations, trends and patters of urbanization, dynamics of urban development and migration in Gujarat. This study particularly focuses on establishing a link between migration and urbanization using district level data on urbanization. This study is unique in the sense that previous studies have failed to capture the interstate migration and levels of urbanization in the state of Gujarat in India. Recent census data show a substantial increase in the census towns in Gujarat in the vicinity of the developed corridor and within the influence areas of large metropolitan cities. This paper aims to analyze the trends and emerging patterns in the levels of urbanization at the district level. It attempts to understand the inequalities in the distribution of urban population using the GINI coefficient of different size-class towns during the 2001 and 2011 censuses. It also tries to map the distribution of the urban population at the district level to show the emerging pattern. Emerging trends and the existing network of the census towns of 2011 have also been mapped to provide the idea of regional distribution. The existing urbanization pattern in Gujarat matches with the industrial development. It reminds colonial experiences of induced industrialization, attracting colossal in-migration and higher urbanization. The migration pattern during the last two census periods shows that respective districts of the above-mentioned cities are attracting in-migration due to the early post-independence industrialization period. We have calculated the net contribution from migration to the levels of urbanization using D-2 Series migration data from the census of India for the years 2001 and 2011. It shows that Central Gujarat, Saurashtra and South Gujarat have gained more due to migrations from other states to sustain their industrial development, leading to rapid and higher levels of urbanization in these regions. However, the future of urbanization in the state will depend on carefully selecting industrial activities that are sustainable in the long run.